THE FIRST GENERA OF PLANKTONIC FORAMINIFERS: MORPHOGENESIS, DEVELOPMENT, AND EXPANSION IN THE JURASSIC - Kuznetsova K.I. (My University, 2003)
Characteristic features of the initial evolutionary stage of planktonic foraminifers are considered. It is shown that, in the Early Jurassic, they display a high taxonomic and morphological diversity and are represented by various morphotypes. The basic structural types of the shell and its morphological elements were formed at the very early developmental stage of this group. The genera of planktonic foraminifers first discovered in the Lower Jurassic of central Turkey are described and shown in figures. In addition, the taxonomic composition and distribution of the genera that were initially discovered in later beds but have not been registered in the Lower Jurassic are discussed.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская